The Impact of Leadership on Organizational Development – Evidence from Fashion Maker Ltd. - Gopal Chandra Saha; Aditi Roy; S.M. Akber (Annals of Management and Organization Research, 2025)
Purpose: This study explores and analyzes the various leadership traits within the context of contemporary management practices to develop the organization; focusing on ‘Fashion Maker Ltd.’ by analyzing and applying the theoretical insights of a real-world case study. Research Methodology: Various leadership philosophies and their implications for business firms have been studied through literature review and one case study on ‘Fashion Maker Ltd. Has been focused to get the practical insights of leadership practices. A structured questionnaire with open-ended and close-ended questions, 100 employees from Fashion Maker Ltd were surveyed through random sampling techniques to ensure the equal chance of participating opportunities. Results: In this study, several important traits for effective leadership, including emotional intelligence, integrity and communication skills have been found more highlighted to positively correlated with higher levels of employee satisfaction and perceived organizational success. Limitations: Limited sample size of 100 employees from a single company may not fully represent the broader population. Contribution: This study will provide the valuable insights into the specific traits that contribute on organizational success through effective leadership. Novelty: Combining a theoretical review with a case study provides a unique perspective on letting know the leadership theories application in real world scenario.